Shackled by Patriarchy and Poverty - Smita Tanaya (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This article discusses how patriarchal elements of society and culture, in conjunction with poverty, is necessary to comprehend the domestic violence experienced by women. This article departs from a qualitative case study of the experiences of women in Taekas Village, North Central Timor, East Nusa Tenggara, and Pondok Batu Village, Labuhanbatu, North Sumatra, and seeks to obtain a comprehensive and in-depth understanding of how patriarchy and poverty contribute to domestic violence. This article emphasizes that, although domestic violence knows no class, religious, or geographical boundaries, rural women who live in poverty are more vulnerable to domestic violence. This article is hoped to shed light on domestic violence in Indonesia, thereby increasing awareness and providing further impetus for eradicating said practice.